Integrating local language as acceptance act response strategies in academic discourse: Sociopragmatic approach - Dian Anik Cahyani; Banu Wicaksono (Celtic : A Journal of Culture, English Language Teaching, Literature and Linguistics, 2026)
Pragmatic competence plays a crucial role in communication, particularly in academic discourse. Previous studies on sociopragmatics have largely focused on second language learners’ speech acts; however, limited attention has been paid to adult learners in higher education who strategically employ the local language. Specifically, this research examines Acceptance Act Response (AARs) strategies through a sociopragmatic lens and remains underexplored in multilingual academic contexts in Indonesian higher education. This research aims to investigate how adult learners in higher education utilise local language in academic discourse as a sociopragmatic for expressing AARs strategies. This research adopts a qualitative approach, and the data are described descriptively. The research was conducted in Indonesian Language Education at PGRI Jombang University. Data were collected through classroom observations and audio recordings of academic interactions involving local language use. The recorded data were analysed descriptively. The findings reveal that adult learners frequently use local language as a pragmatic strategy to express AARs in academic discourse. Several AARs strategies were identified, including: absolution, dismissal, formal, thanking, intensifiers, requests, expressing emotion, and questioning. Among these strategies, absolution was the most frequently used (25.3%), while expressing empathy was not observed in the data. These patterns indicate that local language serves as an effective resource for managing social relations and maintaining pragmatic appropriateness. It implies that lecturers should pay closer attention to instructional practices to support the development of adult learners’ pragmatic competence. Integrating awareness of the local language into academic instruction can enhance learners’ sociopragmatic competence and reduce the risk of pragmatic failure.